Smart Tag를 이용한 컨테이너의 GPS 위치 추적 시스템 개발 - 金?完(Dong-Wan Kim); 朴志浩(Jee-Ho Park) (전기학회 논문지 P권, 55(4), 2006)
In this paper, we explore a novel transportation container in the marine terminals. The container includes Smart Tag embedded with radio frequency(RF) chips, which is used to access information about productions and possibly incorporated with GPS systems for integrated managements of them. The proposed mechanism is valuable for decreasing cost, increasing satisfaction of customers, and preventing economic loss due to production missing, thus increase of economic efficiency is highly anticipated. Consequently, accurate and proficient management is considerably accomplished in overall procedures of inventory and currency by means of the proposed systems.